Enhancing bandwidth and efficiency in GaN LEDs for VLC systems - Mohd Nor, Norhanis Aida; Wan Ibrahim, Wan Nur Amierha (IEEE Photonics Society, Malaysia Chapter, 2025)
Gallium nitride (GaN) light-emitting diodes (LEDs) are essential for visible light communication (VLC), enabling high-speed data transmission and energy-efficient lighting. However, c-plane GaN LEDs face limitations due to polarization fields and the quantum confined Stark effect (QCSE), restricting bandwidth and data rates. Advances in semi-polar and non-polar GaN structures have enhanced bandwidth, supporting gigabit-per-second VLC performance. Optimizing the active region through quantum well thinning and hybrid quantum dot integration further boosts modulation speeds. Additionally, Europium (Eu3+) doping provides high-color-purity red emission and faster recombination, improving bandwidth and reducing efficiency droop. This review high-lights these innovations for high- speed VLC systems.